2005
DOI: 10.1007/s10875-005-2818-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of CD4 Counts Among HIV-Negative Ethiopians: Role of Body Mass Index, Gender, Cigarette Smoking, Khat (Catha Edulis) Chewing, and Possibly Altitude?

Abstract: To study the determinants of CD4% and CD4 counts among HIVnegative Ethiopians, and to identify factors susceptible to explain the low CD4 counts observed among Ethiopian subjects. Cohort studies among factory workers in Akaki and Wonji, Ethiopia. Clinical and laboratory examinations, including determination of HIV serological status and T-cell subsets, were performed during follow-up visits every six months. In addition, micronutrients (retinol, carotenoids, tocopherol, transferrin receptor, and selenium) plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
5
27
1
1
Order By: Relevance
“…Univariate and multivariate analyses further indicated that there is a dose-response effect of smoking, with greater number of cigarettes smoked per day associated with an increasing number of both CD4ϩ and CD8ϩ lymphocytes in the peripheral blood of HIV-negative women. Our finding of a positive association between CD4 cell count, smoking, and BMI are consistent with results of a similar study among HIVnegative Ethiopians [7]. However, correlates of CD8 cell counts were not reported in that study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Univariate and multivariate analyses further indicated that there is a dose-response effect of smoking, with greater number of cigarettes smoked per day associated with an increasing number of both CD4ϩ and CD8ϩ lymphocytes in the peripheral blood of HIV-negative women. Our finding of a positive association between CD4 cell count, smoking, and BMI are consistent with results of a similar study among HIVnegative Ethiopians [7]. However, correlates of CD8 cell counts were not reported in that study.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 22 HIV negative women were excluded, because CD4 and CD8 cell counts were unavailable in these participants. Subjects in the original cohort contributed a median (range) of 11 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) visits and those in the new cohort contributed 3 (1-4) visits to the analysis. Baseline characteristics of the study participants are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…214 Nevertheless, other studies have not found relatively low serum Se in HIV-1-infected subjects, suggesting that its deficiency in HIV-1 infection may be most likely to occur in subjects with poor diets, such as intravenous drug abusers and those living in poverty. 215,216 Thus, maintaining an optimal Se status in HIV-1 patients may help to increase the enzymatic defence, improve general health and reduce their risk of hospitalization for opportunistic infections and complications. 217 …”
Section: Hivmentioning
confidence: 99%
“…Our patient was severely malnourished and this is also a cause of immunodeficiency. A significant reduction of the CD4 lymphocytes can occur in conditions with no HIV infection 16 , including severe wasting, as described in Ethiopia 17 .…”
Section: Discussionmentioning
confidence: 87%